Pengaruh Kerjasama Tim Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Telkom Akses Parepare - Nadya Diani Putri; Muh. Ichwan Musa; Agung Widhi Kurniawan (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research aims to determine the influence of teamwork and work discipline on employee performance at PT. Telkom Access Parepare. The sample in this study was 86 people, namely all employees at PT. Telkom Access. The data used are primary and secondary data obtained from distribution via questionnaires. The results of this research show that there is a significant influence between the variables Teamwork (X1) and Work Discipline (X2) on employee performance (Y) as proven through analysis of the T test and f test, where variable X has t count > t table (X1) 3.596 > 1.663 and (X2) 3.140 > 1.663. The results of this research also show that the calculated f value > table f (0.002 < 0.5). And R square is 0.541%.